Preliminary study of the mechanism of action of ethanamizuril against Eimeria tenella - Li, Xueyan; Chen, Huiya; Zhao, Qiping; Zhang, Lifang; Zhang, Keyu; Wang, Xiaoyang; Wang, Mi; Liu, Yingchun; Wang, Chunmei; Xue, Feiqun; Fei, Chenzhong (Parasitology research (1987), 2020)
Ethanamizuril (EZL) is a novel triazine compound with excellent anticoccidial activity. We carried out a preliminary investigation of the effects of EZL on the different life cycle stages of Eimeria tenella . EZL mainly acted on the schizogony stage, with peak activity during the second-generation merozoite stage. We also studied the possible target of EZL by identifying the majorly differentially expressed gene affected by EZL in second-generation merozoites using real-time polymerase chain reaction, and screening for surface antigen proteins (SAGs). The relative expression levels of SAGs were compared by Western blot analysis showing that expression levels of surface antigen family member (SAGfm) and SAG19 were significantly downregulated by EZL. Immunofluorescence analysis indicated that SAGfm and SAG19 were localized on the surface of second-generation merozoites. In addition, fluorescence signals were significantly stronger in second-generation merozoites of infected non-medicated control (INC) group compared with that of the EZL group. Therefore, it was speculated that SAGs might be a potential target of EZL action. The inhibitory effects of anticoccidial drugs on SAG levels in coccidia thus warrant further research.